Existence of Solutions for Quasilinear Elliptic Equations with Unbounded Coefficients on RN (Journal of Partial Differential Equations, 2008)
" In this paper a class of p-Laplace type elliptic equations with unbounded coefficients on R^N is considered. It is proved that there exist radial solutions on R^N. On sufficiently large ball, radial and nonradial solutions are obtained. Finally, some necessary conditions for the existence of solutions are given."
Keywords: Radial and nonradial solutions; singular minimization problem; Derrick-Pohozaev identity; Caffarelli-Kohn-Nirenberg inequality